Varian Islam Nusantara: Jawa, Minangkabau dan Gorontalo - Donald Qomaidiansyah Tungkagi (Jurnal Lektur Keagamaan, 2017)
This article discusses how the encounter of Islam and culture in Indonesia, and how Islam on one hand  affects culture and on the other hand it is influenced by culture. The encounter between Islam and local culture has formed a new habitat that is later called the Islamic Nusantara tradition. The findings in this article prove that the interaction of Islam with local culture occurs in a socio-historical context influenced by the pattern of the spread of Islam in the archipelago. By using the theory of Taufik Abdullah in this article the author compares the three variants of Islamic Nusantara with the pattern and uniqueness of each form: a) Javanese variant, there is a process of acculturation between Islam and culture which are equally strong. The Javanese Islamic variant describes the result of a reconciliation process between identity, belief and the style of Javanese and Islam as "Mystic Synthesis". B) Minangkabau variant, born from "Negotiation of Islam and Adat" as a very thick area of Islamic and customary nuances make the dimensions in Islamic variants in Minangkabau cannot be separated from the conflict between the two parties who gave the role. C) Gorontalo variant, with different Islamization process with other kingdoms in the Nusantara in general. Since the early period of Islamic encounter with Gorontalo culture, there has been more tangible "Integration between Islam and Adat". Keywords: Java, Minangkabau, Gorontalo, Islam NusantaraArtikel ini mendiskusikan bagaimana perjumpaan Islam dan budaya di Indonesia, dan bagaimana Islam pada satu sisi berpengaruh terhadap budaya dan di sisi lain dipengaruhi oleh budaya. Perjumpaan antara Islam dan budaya lokal telah membentuk habitat baru yang belakangan disebut tradisi Islam Nusantara. Temuan dalam artikel ini membuktikan bahwa interaksi Islam dengan budaya lokal terjadi dalam konteks sosio-historis yang dipengaruhi pola penyebaran Islam di kawasan Nusantara. Dengan menggunakan teori Taufik Abdullah dalam artikel ini penulis membandingkan tiga varian Islam Nusantara dengan corak dan keunikannya masing-masing diantaranya: a) Varian Jawa, terjadi proses akulturasi antara Islam dan budaya yang sama-sama kuat. Varian Islam Jawa menggambarkan hasil proses rekonsiliasi antara identitas, keyakinan serta gaya Jawa dan Islam ini dengan sebutan “Sintesis Mistik”. b) Varian Minangkabau, lahir dari “Negosiasi Islam dan Adat” sebagai wilayah yang sangat kental nuansa Islam dan adat membuat warna dalam varian Islam di Minangkabau tidak lepas dari dari konflik antara dua pihak yang memberi peranan tersebut. c) Pola Gorontalo, dengan proses Islamisasi yang berbeda dengan kerajaan-kerajaan di Nusantara pada umumnya. Sejak periode awal perjumpaan Islam dengan budaya Gorontalo lebih berwujud “Integrasi antara Islam dan Adat”.Kata kunci: Jawa, Minangkabau, Gorontalo, , Islam Nusantara